2005
DOI: 10.1614/ws-04-162r.1
|View full text |Cite
|
Sign up to set email alerts
|

Brassica cover cropping: I. Effects on weed and crop establishment

Abstract: The Brassicaceae contain glucosinolates, which hydrolyze to form compounds toxic to plants, fungi, nematodes, and certain insects. Lower weed density and biomass in crops grown following incorporation of brassica cover crops suggest that they may contribute to weed management in agricultural systems. Field experiments were conducted to determine whether incorporated brassica cover crops, including canola, rapeseed, and yellow mustard, reduce subsequent weed and crop establishment; a companion paper describes s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
119
3
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(128 citation statements)
references
References 33 publications
5
119
3
1
Order By: Relevance
“…However, flax seed yield was higher after wheat than canola both sites in all years. The effect may be due to a number of factors, including some degree of allelopathy from canola residue (Haramoto and Gallandt 2005), early-season competition from volunteer canola plants or restriction in mycorrhizal colonization after canola. In a study evaluating sequencing of 10 different crops in North Dakota, Tanaka et al (2005) noted that flax seeded on canola was intermediate in yield in the first year of the study when moisture was 186% of normal, but produced the second lowest yield, after flax seeded on flax, in the second year when precipitation was 104% of normal.…”
Section: Early-season Biomassmentioning
confidence: 99%
“…However, flax seed yield was higher after wheat than canola both sites in all years. The effect may be due to a number of factors, including some degree of allelopathy from canola residue (Haramoto and Gallandt 2005), early-season competition from volunteer canola plants or restriction in mycorrhizal colonization after canola. In a study evaluating sequencing of 10 different crops in North Dakota, Tanaka et al (2005) noted that flax seeded on canola was intermediate in yield in the first year of the study when moisture was 186% of normal, but produced the second lowest yield, after flax seeded on flax, in the second year when precipitation was 104% of normal.…”
Section: Early-season Biomassmentioning
confidence: 99%
“…Glucosinolates occur in many plant species, but are widely known to be produced by species within the Brassicaceae family ( Figure 2) (Haramoto and Gallandt 2005;Malik et al 2008;Mithen 2001). Members of this family include: wild radish (Raphanus raphanistrum L.), white mustard (Sinapis alba L.), turnip (Brassica campestris L.), and rapeseed (Brassica napus L.).…”
Section: Glucosinolatesmentioning
confidence: 99%
“…Members of this family include: wild radish (Raphanus raphanistrum L.), white mustard (Sinapis alba L.), turnip (Brassica campestris L.), and rapeseed (Brassica napus L.). Glucosinolates, secondary metabolites containing sulfur and nitrogen, are enzymatically hydrolyzed by myrosinase in the presence of water to form isothiocynates, the active allelochemicals (Haramoto and Gallandt 2005;Norsworthy and Meehan 2005;Petersen et al 2001;Price et al 2005). Previous research examining extracts from glucosinolate-producing plant species have shown inhibition of other species through reduced germination, reduced seedling emergence and reduced size, as well as delayed seed germination (Al-Khatib et al 1997;Brown and Morra 1996;Malik et al 2008;Norsworthy et al 2007;Wolf et al 1984).…”
Section: Glucosinolatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although complete season-long weed suppression using only glucosinolateproducing plant residues seems unattainable, future studies should continue to test the effects of utilizing higher concentrations of seed powder treatment, especially under field conditions (Haramoto and Gallandt, 2005;. Increased treatment concentrations should improve the longevity of allelopathic compounds in the face of heavy precipitation.…”
Section: Concentration Effects and Multiple Applicationsmentioning
confidence: 99%